Tlingit men and boys pose in ceremonial dress, Hoonah, Alaska, ca. 1900-1923. - Andrews, Clarence Leroy, 1862-1948
Men and boys pose in street with miniature cannon. They wear embroidered, beaded & button tunics and several have headdresses. Man in front wears a Chilkat blanket over his shoulders and a ring in his nose. Row of buildings visible in background. Caption on image: Hoonah Indians in dance costume